International Maritime Law Strategy in Maritime Boundary Disputes Using Negotiation and Mediation : Analysis of Island Cases Sipadan and Ligitan - Derys Cahyanto; Abintoro Prakoso; Evi Dwi Hastri; Fitri Annisa Putri; Herowati Poesoko (International Journal of Law, Crime and Justice, 2024)
This article discusses the importance of reaching mutually beneficial solutions in international conflicts, focusing on negotiation and mediation as key elements. Negotiation allows both parties to resolve each other's differences, while mediation facilitates dialogue and promotes compromise. This research uses normative legal research methods with a statutory approach and case approach to analyze relevant laws and regulations related to the Indonesia-Malaysia maritime boundary, using the technique of collecting legal materials for literature studies. These disputes also impact social, political, economic, and environmental life, and both countries must accept the consequences of the Indonesia-Malaysia maritime dispute, such as dispute resolution costs, potential conflicts, and environmental impacts. The results of this study show that negotiations aim to achieve mutually beneficial solutions by providing a forum for communication, identifying common interests, constructive negotiations, and dialogue with regional, national, or international organizations such as the United Nations. Meanwhile, mediation plays an important role in reaching mutually beneficial solutions, assisting effective communication, information and education, claims actions, compromises, facilitating the negotiation process, and reaching mutual agreements.